Book Review: Ensor, Jonathan, Berger, Rachel and Huq, Saleemul, editors. 2014: Community-based Adaptation to Climate Change: Emerging Lessons. (January 2016) - Donaldson, Chris
Ensor, Jonathan, Berger, Rachel and Huq, Saleemul, editors. 2014: Community-based Adaptation to Climate Change: Emerging Lessons . Rugby, UK: Practical Action Publishing. Chapters 11, 216 pp.. £17.95 (paperback). ISBN: 9781780447919.